Persistent NK cell deficiency associated with pulmonary cryptococcosis - Martin Martinot; Shu Shun Li; Catherine Farnarier; Cléa Dubrou; Christelle Piperoglou; Christopher H. Mody; Frederic Vely (Annals of Clinical Microbiology and Antimicrobials)
Abstract We describe pulmonary cryptococcosis in a 28-year-old previously healthy man. Exhaustive immunological investigations revealed a primary NK cell deficiency associated with a secondary impaired anti-Cryptococcus CD8 lymphocyte response and the expansion of a CD8Vβ14 + T cell clone. This case illustrates the potential role of NK cells in immunity against Cryptococcus.